Few-layered-graphene/zirconia composites: Single-step powder synthesis, spark plasma sintering, microstructure and properties. Issue 5 (May 2022) - Flaureau, Andréas; Weibel, Alicia; Chevallier, Geoffroy; Esvan, Jérôme; Laurent, Christophe; Estournès, Claude
Highlights: Few-layered-graphene (FLG) films of very homogeneous thickness have been deposited on the surface of the grains of a 3YSZ ceramic powder. A high level of densification of these composite materials has been achieved by using the Spark Plasma Sintering process. FLG's high levels of distribution at grain boundaries result in electrically conductive materials with less than 1.98 vol.% carbon content. Materials with anisotropic electrical conductivity (ratio σ⊥ / σ// about 4) are obtained. The toughness of composites increases with the carbon content suggesting a slight reinforcing role of the FLG. Abstract: The chemical vapor deposition of carbon is performed onto a commercial yttria-stabilized zirconia (3YSZ) powder bed. This produces few-layered-graphene (FLG) film uniformly covering the 3YSZ grains, without the manipulation of any pre-existing nanocarbon in the form of graphene platelets. The powders are then consolidated by spark plasma sintering, producing specimens where FLG is located along the grain boundaries of the 3YSZ matrix, which is below 0.3 μm in grain size. The samples are characterized by Raman spectroscopy, X-ray photoelectron spectroscopy, scanning and transmission electron microscopy. The pure 3YSZ exhibits higher toughness and fracture strength compared to composites, but the trend is that their toughness increases upon the increase in carbon content. Crack-deflection and crack-bridging are observed. The composites are electrically conducting with a percolation threshold between 1.48 and 1.98 vol.% of carbon, reflecting the continuous nature of the FLG film over very long distances.